Comparison of different exercises on muscle thickness, pain, and disability in patients with low back pain: A randomized controlled study - Elbasti, Muhammet Sahin; Yentur, Songul Baglan (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2026)
Objectives: The aim of this study was to compare the effects of stabilization exercises, McKenzie exercises, and home exercises on pain, disability, and muscle thickness of the transversus abdominis (TrA), multifidus (MF) and gluteus maximus (Gmax) in patients with low back pain. Patients and methods: The prospective, randomized controlled study was conducted between November 7, 2022, and February 7, 2023. A total of 45 patients (30 males, 15 females; mean age: 40.93 +/- 5.31 years; range, 30 to 50 years) with low back pain were randomly divided into three groups: stabilization exercise group (SG), McKenzie exercise group (MG), and home exercise group (HG). Pain intensity and disability were evaluated using the Visual Analog Scale and the modified Oswestry Disability Index. Ultrasonographic imaging was used to assess TrA, MF, and Gmax muscle thickness before and after an eight-week intervention program. Results: There were no significant differences in baseline demographic characteristics among the groups (p>0.05). After treatment, statistically significant improvements were observed in pain, modified Oswestry Disability Index scores, and muscle thickness (TrA, MF, and Gmax) in the SG and MG (p<0.05). In the HG, significant improvements were found in pain and some muscle thickness measurements, but no significant change was observed in disability (p>0.05). Comparisons among the groups showed that SG demonstrated significantly greater improvements in disability scores (p=0.008) and muscle thickness (p<0.001) compared to HG. The SG also had superior results in TrA, MF, and Gmax muscle thickness when compared to MG and HG (p<0.05). Conclusion: Stabilization exercises were found to be more effective in improving deep trunk muscle (TrA and MF) and Gmax thickness, as well as reducing disability compared to McKenzie and home exercise programs. McKenzie exercises also provided significant improvements in muscle thickness and pain, whereas the home exercise program showed limited effects. The results emphasize the importance of supervised exercise interventions, particularly stabilization exercises, in managing low back pain.
Keywords: Low back pain; McKenzie exercises; muscle thickness; stabilization exercises